TRH-receptor mobility and function in intact and cholesterol-depleted plasma membrane of HEK293 cells stably expressing TRH-R-eGFP - Brejchová, Jana; Sýkora, Jan; Ostašov, Pavel; Merta, Ladislav; Roubalová, Lenka; Janáček, Jiří; Hof, Martin; Svoboda, Petr (Biochimica et biophysica acta, 2015)
UNLABELLED: Here we investigated the effect of disruption of plasma membrane integrity by cholesterol depletion on thyrotropin-releasing hormone receptor (TRH-R) surface mobility in HEK293 cells stably expressing TRH-R-eGFP fusion protein (VTGP cells). Detailed analysis by fluorescence recovery after photobleaching (FRAP) in bleached spots of different sizes indicated that cholesterol depletion did not result in statistically significant alteration of mobile fraction of receptor molecules (Mf). The apparent diffusion coefficient (Dapp) was decreased, but this decrease was detectable only under the special conditions of screening and calculation of FRAP data. Analysis of mobility of receptor molecules by raster image correlation spectroscopy (RICS) did not indicate any significant difference between control and cholesterol-depleted cells. Results of our FRAP and RICS experiments may be collectively interpreted in terms of a "membrane fence" model which regards the plasma membrane of living cells as compartmentalized plane where lateral diffusion of membrane proteins is limited to restricted areas by cytoskeleton constraints. Hydrophobic interior of plasma membrane, studied by steady-state and time-resolved fluorescence anisotropy of hydrophobic membrane probe DPH, became substantially more "fluid" and chaotically organized in cholesterol-depleted cells. Decrease of cholesterol level impaired the functional coupling between the receptor and the cognate G proteins of Gq/G11 family. IN CONCLUSION: the presence of an unaltered level of cholesterol in the plasma membrane represents an obligatory condition for an optimum functioning of TRH-R signaling cascade. The decreased order and increased fluidity of hydrophobic membrane interior suggest an important role of this membrane area in TRH-R-Gq/G11α protein coupling.
Keywords: kinetika; algoritmy; transport proteinů; Algorithms; proteiny vázající GTP - alfa-podjednotky Gq-G11; Protein Binding; HEK293 Cells; FRAP; Fluorescence Recovery After Photobleaching; Cell Membrane; difenylhexatrien; Microscopy, Confocal; receptory thyroliberinu; GTP-Binding Protein alpha Subunits, Gq-G11; Cholesterol; TRH-R-eGFP mobility; konfokální mikroskopie; Green Fluorescent Proteins; DPH fluorescence; HEK293 buňky; difuze; fluorescenční polarizace; Humans; Receptors, Thyrotropin-Releasing Hormone; RICS; Diffusion; vazba proteinů; zelené fluorescenční proteiny; Kinetics; buněčná membrána; Protein Transport; Diphenylhexatriene; G protein coupling; Fluorescence Polarization; lidé; cholesterol